ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI VOLUME PRISMA DENGAN FONGâS SHCEMATIC MODEL FOR ERROR ANALYSIS DITINJAU DARI GAYA KOGNITIF SISWA - NurussafaÃ¢Â€Â™at, Fitri Andika; Sujadi, Imam; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: This study aims to find out studentsâ error in solving stories problems on prism volume using fongâs shcematic model for error analysis viewed from the studentsâ cognitive style. This study was conducted in SMP IT Ibnu abbas Klaten in the academic year of 2013/2014. This study is a qualitative study. The technique used in selecting the research subjects was purposive sample. The subjects used in this study were 6 students taken from grade VIII. The result is: (1) the errors experienced by students with field dependent type is more dominant than operational errors, and mathematical themes errors, (2) the errors experienced by students with field independent type is more dominant than language errors, (3) the factors that caused students with field dependent type to make mistakes in solving prism volume word problems based were: the inadvertence on reading the problems, the forgetfulness, in a hurry to finish, the effect of the previous mistakes, and the lack of understanding on the sequence of solving the problems, (4) the factors that caused students with field independent type to make mistakes in solving prism volume problems based were: the assumption that the symbol (=) might be replaced with the symbol (:), the desire to quickly finish the problems, in a hurry in solving the problems, the habit of incomplete problems writing, the effect of the previous mistakes, the lack of the steps mastery of solving the given problems.Keywords: Error analysis, Prism Volume, Fongâs Shcematic Model For Error Analysis, Cognitive style.